APPLICATION OF SEVERALSLURRYBIOGAS ATDIFFERENT LEVEL TO THE GRO WTH AND YIELD OF Indigofera zollingeriana - I K., Wirawan; Kusumawati, N. N. C.; Trisnadewi, A. A. A. S. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
Organic fertilizer is required to improve the growth and yield of Indigofera zollingeriana. One  could be used is biogas slurry which is excess product of biogas. The experiment aims to find out growth and yield of Indigofera zollingeriana leguminose given different kinds and level of slurry. The experiment carried out for 10 weeks at Laboratory Greenhouse of Feed Plant, Faculty of Animal Husbandry, Udayana University. Experiment design was used completely randomize design (CRD) factorial pattern with two factors. The first factor was sources of slurry: which were cattle slurry (S), pig slurry (B), and cattle bio-slurry (P), the second factor was level of slurry: without slurry (0 ton/ha) (D 0 ), 10 ton/ha (D 10 ), 20 ton/ha (D 20 ), and 30 ton/ha (D 30 ). There were combination of 12 treatments and each of combination was repeated four times, so there were 48 pots study. Variabeles observed were growth, yield, and growth characteristic. Results of the study showed that cattle bio-slurry gave the highest  growth, yield, and growth characteristics compare with cattle and pig slurry. Indigofera zollingeriana which were given 10 ton/ha (D 10 ) resulted in thegive the highest growth, yield, and growth characteristics compare with 0 ton/ha (D 10 ), 20 ton/ha (D 20 ), and 30 ton/ha (D 30 ). There was no interaction between the type and level of fertilizer against growth and forage yield. It was concluded that cattle bio-slurry of 10 ton/ha (D 10 ) geve the best growth and yield of Indigofera zollingeriana and there was no interaction between kinds and level of slurry. Keywords: slurry, level of biogas slurry, Indigofera zollingeriana, growth, yield